Language Attributes in the Kaskus Community: English - Moh. Shofi Zuhri; Nashihin, Muhammad (Institut Agama Islam Tarbiyatut Tholabah, 2023)
Community is a form of the result of human social interaction. The formation of this community is based on many things and provides various kinds of impacts in social life, one of these impacts is the emergence of certain language attributes in a community and these language attributes can be different from those in other communities. This also occurs in one of the largest online communities in Indonesia, Kaskus, where members of the community have special language attributes in interactions between members. The language attribute that appears in this community is a marker, either implicitly or explicitly, that those who use the language attribute are part of that community. In this study, the Kaskus online community has a language attribute in the form of registers used in greeting and promotion interactions.